Machine Learning 2012
DOI: 10.4018/978-1-60960-818-7.ch319
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy Prediction by Supervised Machine Learning Techniques

Abstract: It is very important for financial institutions which are capable of accurately predicting business failure. In literature, numbers of bankruptcy prediction models have been developed based on statistical and machine learning techniques. In particular, many machine learning techniques, such as neural networks, decision trees, etc. have shown better prediction performances than statistical ones. However, advanced machine learning techniques, such as classifier ensembles and stacked generalization have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…They are widely used in the literature (see e.g. Hsieh, 2005;Tsai et al, 2011;West et al, 2005). The information contained in these data sets is shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are widely used in the literature (see e.g. Hsieh, 2005;Tsai et al, 2011;West et al, 2005). The information contained in these data sets is shown in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…outliers) to reduce prediction errors during the training of a classifier (Hsieh, 2005). Related work has shown that advanced machine learning techniques outperform single classifiers (West et al, 2005;Tsai et al, 2011). For instance, Hsieh ( 2005) constructed a hybrid classifier by combining the k-means clustering method and a neural network model, which shows that the hybrid classifier can provide greater prediction accuracy than the single neural network model.…”
Section: Introductionmentioning
confidence: 99%
“…It uses a huge number of decision trees as base classi ers to construct a forest as multiple decision trees or forests can perform better than one. Therefore, using combined classi ers or combined learned models, desirable results can be obtained [55]. The model will be trained using samples from the training set selected randomly and with random replacements in each attempt to make sure that each sample has been trained at random and the best-trained model will be chosen to contribute to the nal decision of model construction.…”
Section: Random Forestmentioning
confidence: 99%